CD32+CD4+ T Cells Sharing B Cell Properties Increase With Simian Immunodeficiency Virus Replication in Lymphoid Tissues - Huot, Nicolas; Rascle, Philippe; Planchais, Cyril; Contreras, Vanessa; Passaes, Caroline; Le Grand, Roger; Beignon, Anne-Sophie; Kornobis, Etienne; Legendre, Rachel; Varet, Hugo; Saez-Cirion, Asier; Mouquet, Hugo; et al. (Frontiers in Immunology, 2021)
CD4 T cell responses constitute an important component of adaptive immunity and are critical regulators of anti-microbial protection. CD4+ T cells expressing CD32a have been identified as a target for HIV. CD32a is an Fc receptor known to be expressed on myeloid cells, granulo-cytes, B cells and NK cells. Little is known about the biology of CD32+CD4+ T cells. Our goal was to understand the dynamics of CD32+CD4+ T cells in tissues. We analyzed these cells in the blood, lymph nodes, spleen, ileum, jejunum and liver of two nonhuman primate models frequently used in biomedical research: African green monkeys (AGM) and macaques. We studied them in healthy animals and during viral (SIV) infection. We performed pheno-typic and transcriptomic analysis at different stages of infection. In addition, we compared CD32+CD4+ T cells in tissues with well-controlled (spleen) and not efficiently controlled (jejunum) SIV replication in AGM. The CD32+CD4+ T cells more frequently expressed mark-ers associated with T cell activation and HIV infection (CCR5, PD-1, CXCR5, CXCR3) and had higher levels of actively transcribed SIV RNA than CD32-CD4+T cells. Furthermore, CD32+CD4+ T cells from lymphoid tissues strongly expressed B-cell-related transcriptomic signatures, and displayed B cell markers at the cell surface, including immunoglobulins CD32+CD4+ T cells were rare in healthy animals and blood but increased strongly in tissues with ongoing viral replication. CD32+CD4+ T cell levels in tissues correlated with viremia. Our results suggest that the tissue environment induced by SIV replication drives the accumulation of these unusual cells with enhanced susceptibility to viral infection.